2014
DOI: 10.1111/ijfs.12588
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in dry‐aged loins manufactured with sonicated pork and inoculated with Lactobacillus casei ŁOCK 0900 probiotic strain

Abstract: Summary Selected parameters related to proteolysis were evaluated in dry‐aged loins manufactured with sonicated pork and inoculated with Lactobacillus casei ŁOCK 0900 probiotic strain. Dehydration, pH, water activity and total nitrogen content were not affected by ultrasound treatment. Neither sonication nor inoculation has an influence on L* and a* colour parameters. Sonication significantly influenced the pattern of proteolysis providing higher nonprotein nitrogen content (NPN) and proteolysis index (PI). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
3
12
1
Order By: Relevance
“…Loins inoculated with LAB strains exhibited, in all the sampling times, significantly lower pH ( P < 0.05) than the control sample (C), which underwent spontaneous fermentation. These results correspond with the findings of other authors who confirmed the effectiveness of the inoculation with LAB for acidification of dry‐cured meat products (Stadnik et al ., ; Okoń et al ., 2017a; Wójciak et al ., ). In three sampling times (90, 270, 360 days of storage) significantly ( P < 0.05) lower pH values were observed for loins with Bifidobacterium (BB12) compared to both samples with Lactobacillus .…”
Section: Resultsmentioning
confidence: 99%
“…Loins inoculated with LAB strains exhibited, in all the sampling times, significantly lower pH ( P < 0.05) than the control sample (C), which underwent spontaneous fermentation. These results correspond with the findings of other authors who confirmed the effectiveness of the inoculation with LAB for acidification of dry‐cured meat products (Stadnik et al ., ; Okoń et al ., 2017a; Wójciak et al ., ). In three sampling times (90, 270, 360 days of storage) significantly ( P < 0.05) lower pH values were observed for loins with Bifidobacterium (BB12) compared to both samples with Lactobacillus .…”
Section: Resultsmentioning
confidence: 99%
“…(), the competitive nature of lactic acid bacteria in meat products with low pH, water activity and a high LAB concentration is responsible for the decreased survival of Enterobacteriaceae. The decrease in pH may partly explain the reduction and disappearance of these groups of bacteria, as other authors have observed (Stadnik et al ., ; Wójciak et al ., ; Wójciak et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Considerably, lower results were obtained by Stadnik et al . () in pork sonicated loins with probiotic ( a* = 0.3, b* = 5.1) and Lorezno () in foal ‘Cecina’ for 120 days of ripening ( a* = 4.7, b* = 4.3).…”
Section: Resultsmentioning
confidence: 99%
“…The results of our work correspond to those reported by Skwarek et al (2014) for raw-ripening probiotic ham (a* = 9.7, b* = 6.5) and submitted by Kaya & Aksu (2005) for 'Sucuk' with starter culture included Bifidobacterium BB-12 stored 90 days (a* = 11.8, b* = 7.2). Considerably, lower results were obtained by Stadnik et al (2014) in pork sonicated loins with probiotic (a* = 0.3, b* = 5.1) and Lorezno (2014) in foal 'Cecina' for 120 days of ripening (a* = 4.7, b* = 4.3).…”
Section: Instrumental Colourmentioning
confidence: 89%
See 1 more Smart Citation